Geografi Manusia dalam Perspektif Filsafat Ilmu - Ita Mardiani Zain; Siti Masitoh; Mochamad Nursalim (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Geography in Indonesia is now specialized, so geography is considered a part of science with physical and human aspects. This idea leads researchers to confine themselves to the auxiliary sciences of geography and often cuts other branches of science. Geology is often considered a science if it is not recognized by other scientists that the existence of geography in the future will be threatened. This study aims to explain human geography from the perspective of philosophy of science which includes ontology, epistemology and axiology of human geography. The ontology of human geography is part of the science of geography. The methods used in the landscape are complex in terms of geography, environment Â and Â geography. Epistemologically, human geography uses qualitative and quantitative methods based on extensive research. Axiologically, the existence of human geography is very important because it supports the development.